First Fifty Cases with En-Bloc Holmium Laser Enucleation of the Prostate - Georgi Georgiev; Nikolay Kolev; Vladislav Dunev; Boyan Atanasov (Journal of Biomedical & Clinical Research)
In the last decade, the Holmium Laser Enucleation of the Prostate (HoLEP) has become the new gold standard for surgical treatment of benign prostatic hyperplasia (BPH). This treatment has several modifications, and the latest one is en bloc (single piece) enucleation. This new method reduces the operative time and risk of early incontinence. The long-term effect is much better than transurethral resection of the prostate (TURP). We applied an effective method for treating benign prostatic hyperplasia with maximum safety, minimal hospital stays, short operative time, and minimal complications. We operated on 50 patients with BPH with a prostate volume between 30-120 cc. Transrectal ultrasound, uroflowmetry, PSA test, IPSS (International Prostate Symptom Score), residual urine, digital rectal examination, and laboratory blood and urine tests were performed preoperatively. We used Holmium laser (Auriga XL) 50 W, 600 μm fiber and morcellator (Richard Wolf PIRANHA). During the procedure, the laser’s operating power was 36 W. En bloc Holmium enucleation was performed in all patients, followed by morcellation of the prostatic tissue. The time for enucleation was 11-52 min, morcellation time - 1-10 min, the weight of the enucleated tissue - 15-100 g, enucleation efficiency - 0.67-3.03 g/min, postoperative catheterization time - 24-72h, and hospital stay was 1 to 3 days. One blood transfusion was required. There were no patients with postoperative incontinence or other complications. We conclude that еn bloc Holmium enucleation in BPH is an effective method of treatment that offers maximum performance combined with short operative time, shorter hospital stays, and minimal risk of complications. The learning curve requires at least twenty cases. The recommended prostate gland size for the initial trial should be between 50-60 cc. Starting with small-sized glands increases the risk of capsule perforation, and the enucleation plane is more difficult to find.